Efeitos do cádmio na morfofisiologia e bioquímica das espécies Peltophorum dubium (Spreng.) Taub. e Mimosa scabrella Benth. em cultivo hidropônico - Oliveira, Gerâne Silva Wertonge de (2020)
Heavy metal toxicity has serious consequences for the environment and man. Among these elements, cadmium (Cd) is considered one of the most harmful. When reaching high levels of contamination in an area, the suppression of vegetation can occur, so the identification of species resistant to this contamination helps in the process of revegetation and decontamination of these places. The species Peltophorum dubium (Spreng.) Taub. and Mimosa scabrella Benth. are Brazilian natives, of fast growth and that occur naturally in Rio Grande do Sul. This study was divided into two chapters. In Chapter I, the objective was to evaluate the effects of Cd on growth and on physiological and morphological variables, and in Chapter II the objective was to evaluate the effects of Cd on the biochemical variables of P. dubium and M. scabrella seedlings in hydroponic and determine the sensitivity or resistance/tolerance of these plants to this element. The experiments were carried out in the greenhouse and in the Physiology and Plant Nutrition Laboratories of the Department of Biology, Federal University of Santa Maria, Santa Maria, RS. The seedlings of both species (obtained by sowing on commercial substrate) after reaching 15 cm in height, were transferred to the hydroponic system for acclimatization, which was composed of a complete nutrient solution. The treatments were represented by adding the following Cd concentrations (in the form of CdCl2) to the solution: 0, 25, 50, 75 and 100 μM. For each species, the experimental design was completely randomized, with four replications consisting of 16 plants each. P. dubium was cultivated in January and M. scabrella in May 2019, but in both experiments the plants remained exposed for 14 days to Cd, and after that period physiological, biochemical and morphological analyzes were performed. The data were subjected to analysis of variance and differentiated means by the Tukey test at 5% probability of error. P. dubium species was shown to be sensitive to Cd even at low concentrations, because the increase in Cd in solution negatively affected photosynthesis, photosynthetic pigment content, morphology of the root system, biomass production and growth in height and root main. The activity of the guaiacol peroxidase (POD) enzyme in P. dubium and M. scabrella was induced even in high concentrations of Cd and reduced the levels of hydrogen peroxide, however this was not able to prevent lipid peroxidation in both species. In the evaluated period, the peroxidation of membrane lipids did not cause damage to the production of biomass, root system architecture and pigment content in plants of M. scabrella in low concentrations. Therefore, M. scabrella can be a species indicated for the recovery of soils contaminated with cadmium up to 50 μM.